Sosialisasi dan Edukasi Pencegahan Perundungan (Bullying) pada Siswa Sdn Ngemplak - Nafarin Zuhaeroh; Mei Setianingsih; Revi Rifatul Muna; Takhta Alfina; Muhammad Zaki ‘Alal Mutaqien; Salis Irvan Fuadi (Nusantara Mengabdi Kepada Negeri, 2026)
Bullying is a common problem in elementary schools and can negatively impact students' psychological and social development, as well as their academic achievement. This community service activity aims to increase students' understanding and awareness of bullying at Ngemplak Elementary School regarding the definition, forms, impacts, and prevention of bullying through outreach and educational activities. The method used was a qualitative approach with case studies, implemented through interactive lectures, discussions, Q&A sessions, and supporting activities such as icebreakers and anti-bullying songs. The results of the activity showed an increase in students' understanding of bullying behavior, a growing sense of empathy, and the courage to reject and reprimand bullying. Student participation was very active and enthusiastic, supported by a fun and communicative learning environment. The school also responded positively, assessing the activity as beneficial in supporting character education and creating a safe and comfortable learning environment. Overall, the outreach and education on bullying prevention at Ngemplak Elementary School has made a significant contribution to building a school culture that is more caring, respectful, and free from bullying.